ANALYSIS OF ELECTROMAGNETIC PROCESS IN COMBINED INDUCTOR SYSTEMS, AS TOOLS FOR STRAIGHTENING OF MODERN CAR - D.O. Voloncevich (National Technical University "Kharkiv Polytechnic Institute", 2015)
The field in combined inductor systems exists only over workpiece, it occurs at only a low-frequency circular magnetic field. In this paper electromagnetic processes in tools of the magnetic pulse attraction (the combined inductor systems) are analyzed. Investigation based on numerical estimations, using previously obtained analytical relations for the excited fields and forces. Calculations are necessary for the successful implementation of straightening metal coatings bodies car. A distribution of relative intensity of magnetic fields to surfaces of sheet workpiece in the centre of a working zone is obtained. The distribution of amplitude tangential component intensity of resulting magnetic field of the surface of sheet metal along the centre of a rectangular coil is received. Feature of the combined induction system is non-uniformly distributed forces of attraction in the work area. The results showed that the calculated working area on the outer surface of sheet workpiece magnetic field strength will be less than 5% of the field strength of a circular low-frequency source. Calculations have shown the effectiveness of the proposed instrument magnetic pulse straightening metal coating bodies car. The actual amplitude of distributed attraction forces are ~ 7.7 MPa.